Blastic Plasmacytoid Dendritic Cell Neoplasm - Lencastre, A (2013)
Blastic plasmacytoid dendritic cell neoplasm is a rare and aggressive hematodermic neoplasia with frequent cutaneous involvement and leukemic dissemination. We report the case of a 76-year-old man with a 2 month history of violaceous nodules and a tumor with stony consistency, located on the head, and mandibular, cervical and supraclavicular lymphadenopathies. Multiple thoracic and abdominal adenopathies were identified on computerized tomography. Flow cytometry analysis of the skin, lymph node and bone marrow biopsies demonstrated the presence of plasmocytoid dendritic cell neoplastic precursor cells (CD4+, CD45+, CD56+ and CD123+ phenotype). After initial clinical and laboratorial complete remission with chemotherapy, the patient died due to relapse of the disease associated with the appearance of a cervical mass with medullary compromise.